Мужской костюм ранних тюрков в китайском искусстве VI—VII вв.: образы "иных" - Яценко, С.А. (Степи Европы в эпоху средневековья, 2009)
The paper analyzes two main groups of images of the Early Turks (almost exclusively noble people. 9 complexes including 14 compositions) in Chinese art. The most ancient of the known images of the Turks of the First Kaghanate era are presented on the Chinese Sogdians’ mortuary beds and sarcophagi of the 2nd half of the 6th c. Later images can be seen on mortuary terracotta figurines of the Early Tang era the 7th - 1st half of the 8th century (the East Kaghanate era).